PENGARUH KUALITAS PELAYANAN, DESAIN PRODUK DAN LOKASI TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA BATIK RENGGANIS DI BUNGATAN SITUBONDO - Yuninda, Zilfiyana; Ediyanto, Ediyanto; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2025)
This study examines the influence of service quality, product design, and location on purchase decisions and customer satisfaction at Batik Rengganis. A quantitative approach was employed, and data were collected through questionnaires distributed to Batik Rengganis customers. The data were analyzed using Partial Least Squares - Structural Equation Modeling (PLS- SEM) version 3.0. The results of the study indicate that service quality and location have a significant influence on purchase decisions, whereas product design does not have a significant effect. Moreover, none of the three independent variables; service quality, product design, and location, have a direct impact on customer satisfaction. Interestingly, purchase decisions were found to have a significant influence on customer satisfaction. However, no mediating effect of purchase decisions was observed in the relationship between the three independent variables and customer satisfaction. This study reveals that although service quality and location play an important role in influencing purchase decisions, these factors alone are not sufficient to ensure customer satisfaction. The findings provide practical implications for Batik Rengganis business owners, highlighting the need to go beyond operational improvements and adopt more comprehensive strategies to enhance customer satisfaction holistically. Furthermore, this study contributes to the marketing literature, particularly within the traditional crafts industry by investigating relationships among variables that have been rarely examined in previous research..